Tweets from the Campaign Trail Researching Candidates' Use of Twitter During the European Parliamentary Elections - Frame, Alex; Mercier, Arnaud; Brachotte, Gilles; Thimm, Caja (Bonner Beiträge zur Medienwissenschaft, 2016)
Hailed by many as a game-changer in political communication, Twitter has made its way into election campaigns all around the world. The European Parliamentary elections, taking place simultaneously in 28 countries, give us a unique comparative vision of the way the tool is used by candidates in different national contexts. This volume is the fruit of a research project bringing together scholars from 6 countries, specialised in communication science, media studies, linguistics and computer science. It seeks to characterise the way Twitter was used during the 2014 European election campaign, providing insights into communication styles and strategies observed in different languages and outlining methodological solutions for collecting and analysing political tweets in an electoral context.